Caring Behavior of Nurses: A Concept Analysis - Viker Albano; Fernando Dela Cruz Calero; Mary Grace Francisco; Maria Christia Ramolete; Daphne Lyn Rivera (Health Notions, 2022)
The aim of this paper is to analyse the concept of caring behaviour of diabetic nurses in terms of its use and definition in the provision and or management of health care services to diabetic patients with COVID 19.  This paper is limited to the context of its use within the hospital care setting. A literature review was conducted wherein out of 30 resources that were assessed, only nine literatures were included. The paper revealed that caring behaviour is a human action, intervention, and emotion as its defining attributes.  Caring behaviour as a human action is the act of a nurse while performing its duties and responsibilities, while as an intervention, it is the action performed to meet the patient’ needs while undergoing treatment. Moreover, as an emotion it conveys empathy, happiness, and concern towards patient’s safety.  It is further inferred that caring behavior is always present in a diabetic nurse whatever case he/she is handling; the acceptance or acknowledgement of the caring behavior of the nurse by a patient may hasten recovery and caring behavior is the core of nursing and cannot be separated from the nursing profession. Keywords: caring behaviour; human action; intervention; emotion; dietic nurses